Fraud Heptagon Analysis in Detecting Fraudulent Financial Statements with the Whistleblowing System as a Moderating Variable An Empirical Study on Consumer Cyclicals Sector Companies Listed on the Indonesia Stock Exchange, 2020–2024 - Erlina Erlina; Iin Rosini; Dian Widiyati (JURNAL ECONOMINA, 2026)
This study examines the influence of the seven elements of the fraud heptagon pressure, opportunity, rationalization, capability, arrogance, ignorance, and greed on fraudulent financial statements, and tests whether the whistleblowing system (WBS) moderates these relationships. Using a quantitative associative design, the research analyzes panel data from 76 consumer cyclicals firms listed on the Indonesia Stock Exchange during 2020-2024 (380 firm-year observations) obtained through purposive sampling. Fraudulent financial statements were proxied by the Dechow F-Score, and the data were analyzed using panel-data regression and Moderated Regression Analysis with EViews 13. The results indicate that pressure, opportunity, rationalization, capability, and greed have a significant positive effect on fraudulent financial statements, whereas arrogance and ignorance do not. The whistleblowing system significantly moderates and weakens the effect of all seven heptagon elements, functioning as a quasi-moderator and confirming its role as a comprehensive internal-control mechanism.